La diplomacia mexicana frente a Europa Central en el periodo de entreguerras. 1918-1940 - López Contreras, Guillermo (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
The end of the Mexican Revolution and the ascension of the emanated different governments of the groups that triumphed in the conflict gave it began to a time full with conflicts and changes. One of the most significant was the gradual nationalization of the Mexican economy, expressed in the Constitution of 1917. In fact, this posture was the one that defined the direction of the international relationships of Mexico during a great part of the period of entreguerras. Companies and foreign groups were threatened their interests in Mexico. The reaction of these groups was, in a first moment, to interfere in the political events that were developed in the country and to be about influencing in the politics of the governments posrevolucionarios. When not achieving their objectives they appealed the governments of their origin countries to request them the protection of these interests. The foreign governments were very informed of happening Mexican and they knew, equally that the interests of their matters were not only in risk, but his own. With everything, the European powers were aware that the only power with real capacity to press the Mexican government was the United States. These circumstances transformed the United States into the paladin of the foreign capitalists in Mexico. At the same time this gave him/her the opportunity to try to subject to their influence sphere to their neighbor of the south without practically competition. The problems outlined by the reclamations of Washington made the relationships between Mexico and the United States to be very tense during several lapses between the end of the Mexican Revolution and the beginning of Second World War.

El fin de la Revolución mexicana y la ascensión de los diferentes gobiernos emanados de los grupos que triunfaron en el conflicto dieron inició a una época llena de conflictos y cambios. Una de la más significativa fue la paulatina nacionalización de la economía mexicana, expresada en la Constitución de 1917. Precisamente, esta postura fue la que definió el rumbo de las relaciones internacionales de México durante una gran parte del periodo de entreguerras. Empresas y grupos extranjeros vieron amenazados sus intereses en México. La reacción de estos grupos fue, en un primer momento, inmiscuirse en los eventos políticos que se desarrollaban en el país y tratar de influir en la política de los gobiernos posrevolucionarios. Al no lograr sus objetivos recurrieron a los gobiernos de sus países de origen para solicitarles la protección de estos intereses. Los gobiernos extranjeros se encontraban bien informados del acontecer mexicano y sabían, igualmente, que no sólo los intereses de sus particulares se encontraban en riesgo, sino los suyos propios. Con todo, las potencias europeas eran conscientes de que la única potencia con capacidad real para presionar al gobierno mexicano eran los Estados Unidos. Estas circunstancias convirtieron a los Estados Unidos en el paladín de los capitalistas extranjeros en México. Al mismo tiempo esto le dio la oportunidad de intentar someter a su esfera de influencia a su vecino del sur sin prácticamente competencia. Los problemas planteados por las reclamaciones de Washington hicieron que las relaciones entre México y los Estados Unidos fueran muy tensas durante varios lapsos entre el final de la Revolución mexicana y el inicio de la Segunda Guerra Mundial.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2008-0011; Opción en historia de América; Diplomacia mexicana; Europa central; Entreguerras; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2379